Statistical Accounting and Classification of Water Resources - Motuzka, O. M. (Statistics of Ukraine, 2025)
The article examines the role of statistical accounting and classification of water resources in ensuring sustainable development, environmental balance, and economic security. Water is not only a fundamental component of the natural environment but also a critical factor in the economic activity, determining the operation of key sectors such as agriculture, industry, energy, and urban infrastructure. In the face of global challenges – freshwater scarcity, water pollution, climate change, and increasing water stress – the development of a reliable system for water statistics becomes crucial. Such a system allows for quantitative and qualitative assessment of water availability, use, management efficiency, and environmental risks. The study contains a review of leading international approaches to water statistics, particularly the SEEA-Water and IRWS frameworks, which integrate hydrological and economic indicators into the national accounting systems. Special attention is paid to conceptual approaches to assessing water as an economic asset, including the notions of water stress, virtual water, water footprint, full-cost pricing, and polycentric water governance. The article substantiates the need to develop a comprehensive system of sustainable water use indicators that includes water intensity, deficit ratios, pollution indices, and water supply reliability metrics. This approach enables tracking of water use dynamics and supports evidence-based decision-making at national and international level. A significant part of the study is devoted to the analysis of water classification systems. International classification approaches are considered, based on renewability, source, geography, quality, and sectoral use. Additionally, the article presents a national classification system that takes into account the legal status of water bodies, their physical form, affiliation with the water fund, economic purpose, and features of accounting in business entities. The findings highlight the need to harmonize national statistical practices with international standards, ensure institutional transparency, engage communities in data collection, and establish an integrated water monitoring system as a foundation for water security and sustainable development.